"As From a State of Death": Schelling's Idealism as Mortalism. Issue 3 (1st September 2016) - Bruno, G. Anthony
ABSTRACT: If a problem is the collision between a system and a fact, Spinozism and German idealism's greatest problem is the corpse. Life's end is problematic for the denial of death's qualitative difference from life and the affirmation of nature's infinite purposiveness. In particular, German idealism exemplifies immortalism – the view that life is the unconditioned condition of all experience, including death. If idealism cannot explain the corpse, death is not grounded on life, which invites mortalism – the view that death is the unconditioned condition of experience. In "Philosophical Letters, " Schelling critiques idealism, arguing that death symbolizes the regulative ideal of a philosophical system's derivation, our striving for which unifies our rational activity. I interpret Schelling's critique as explaining how death puts philosophy into question, an idea he develops in the Freedom essay and Berlin lectures. Death is not a problem to be solved by a system, but represents philosophy's highest yet unrealizable end.